Parametric study of I-shaped shear connectors with different orientations in push-out test - Boursas Farid; Djamel Boutagouga (Fracture and Structural Integrity)
A great deal of research has been conducted to improve the understanding of the behavior of new types of shear connectors. This article presents the study of I-shaped connectors behavior under monotonic load welded in four different orientations in order to get the position which gives the high shear strength and the best ductility. For this purpose, eight push-out test specimens with I-shaped shear connectors with different orientations and dimensions were tested in C20/25 and C30/37 concrete classes. The load-slip behavior and failure modes of the tested connectors are presented and discussed. Furthermore, a non-linear 3D finite element modelling of the push-out test is performed in order to further investigate the influencing parameters on the I-shaped connectors behavior. Hence, a parametric study is carried out by using the established 3D finite elements model to study the influence of concrete strength, connector’s steel grade, reinforcements, height and length of the connector. Both experimental and numerical results show that there is a privilege orientation for which the shear strength of an I-shaped shear connector is significantly higher than that of all other tested orientations.